Alternative Cropping Systems with Limited Irrigation - A. Schlegel; D. Bond (Kansas Agricultural Experiment Station Research Reports, 2019)
A limited irrigation study involving four cropping systems and evaluating four crop rotations was initiated at the Southwest Research-Extension Center near Tribune, KS, in 2012. The cropping systems were two annual systems (continuous corn [C-C] and continuous grain sorghum [GS-GS]) and two 2-year systems (corn- grain sorghum [C-GS] and corn-winter wheat [C-W]). In 2018, corn yields were similar for all rotations, although averaged across the past 6 years, corn yields were greater following wheat than following corn. There were no significant differences in grain sorghum yields in 2018, which was similar to the multi-year average. Wheat yields were near the multi-year average.
Keywords: corn; grain sorghum; winter wheat; deficit irrigation; irrigated crop rotation